RSM-based optimization of a celery–pomegranate–carrot–lemon juice blend - Dikme, Tugba Gul (Journal of Food Technology Research, 2025)
This study aimed to develop and optimize a multi-component vegetable–fruit juice blend using response surface methodology (RSM) to achieve desirable physicochemical and sensory properties. The formulation included pomegranate, carrot, celery, and lemon juices, selected for their complementary nutritional and sensory attributes. A mixture design was employed to assess the effects of varying proportions on pH, total soluble solids (TSS), and color parameters (L*, a*, b*). Significant regression models with high R² values were obtained, confirming the adequacy of the fitted models. The optimal blend was determined as 40.18% pomegranate, 32.19% carrot, 12.63% celery, and 15% lemon juices. Predicted physicochemical values under these conditions were pH 3.93, TSS 8.62 °Brix, L* 55.1, a* 21.1, and b* 8.3. Component contributions were also examined: lemon and celery decreased pH, pomegranate increased TSS and redness, while carrot enhanced lightness and yellowness due to its β-carotene content. Sensory evaluation with ten semi-trained panelists using a nine-point hedonic scale indicated moderate acceptability, with mean scores between 6.78 and 7.08 for taste, flavor, color, and overall preference. These findings highlight the effectiveness of RSM for optimizing complex beverage formulations and demonstrate the potential of this juice blend as a natural, clean-label functional drink. This study represents the first reported optimization of a celery, pomegranate, carrot, and lemon juice blend, highlighting both its novelty and industrial relevance.